Effects of compressibility, three-dimensionality and air cavity on a free-falling wedge cylinder. (1st December 2020) - Wang, Shan; Guedes Soares, C.
Abstract: The effects of fluid compressibility on the motions and hydrodynamic forces of a free-falling wedge are investigated using the Reynolds-Average Navier-Stokes (RANS) equations and volume of fluid (VOF) method which are implemented in the open-source library OpenFoam. The initial slamming, transition, collapse and post-closure stages during the water entry of the wedge with two Froude numbers are simulated using a dynamic mesh method. The interDyMFoam and compressibleInterDyMFoam solvers are applied in 2D and 3D water entry simulations considering multi-phase problems. The influences of the fluid compressibility and three-dimensionality on the acceleration, velocity, vertical motion and pressures on the entry body are studied. The peak values of pressures on the bottom and top surfaces of the wedge during slamming and air cavity closure stage, are analyzed together with the occurrence time of them. Highlights: The effects of fluid compressibility on the motions and hydrodynamic forces of a free-falling wedge are studied using RANS. The initial slamming, transition, collapse and post-closure stages during the water entry of the wedge are simulated. The influences of the fluid compressibility and three-dimensionality on the entry body are studied.